Immunosuppressive therapy and COVID‐19 infection in patients with NMOSD - Un Wai Choi; Xiwen Ai; Hongyan Li; Yong Hao; Xiaoying Yao; Yangtai Guan (Immunity, Inflammation and Disease, 2024)
Abstract Introduction To evaluate whether treated with immunosuppressants in neuromyelitis optica spectrum disorder (NMOSD) shows an effect on the severity and outcomes of COVID‐19 Omicron variant. Methods This is a substudy of a single‐center clinical trial involving human umbilical cord mesenchymal stem cells (hUC‐MSCs) in NMOSD patients. NMOSD patients with hUC‐MSCs treatment, NMOSD patients without hUC‐MSCs treatment, and matched healthy controls (HC) were included. Demographic information, NMOSD‐related clinical features, comorbidities, use of disease‐modifying therapy, COVID‐19 vaccination status, COVID‐19 clinical features, COVID‐19 clinical outcomes, and NMOSD‐related disease activity were obtained through online questionnaires or phone calls. Results The majority of NMOSD patients received long‐term treatment with mycophenolate mofetil (68.8%) or azathioprine (22.9%), and 50% received oral glucocorticoid. During the epidemic, 97.4% of NMOSD patients infected with COVID‐19 had asymptomatic or mild forms, with only two patients (2.6%) requiring hospitalization. None of these patients required tracheal intubation or admission to the intensive care unit. Clinical symptoms were found to be more prevalent in HC groups. Additionally, the HC groups had higher fever‐recorded temperatures. NMOSD patients who received hUC‐MSCs treatment had shorter disease duration than patients who did not receive hUC‐MSCs treatment. Discussion Immunosuppressant‐treated patients with NMOSD have a similar risk of COVID‐19 infection as the general population, but the disease duration is shorter and the clinical symptoms are less severe. Among our NMOSD patients who received hUC‐MSCs treatment, COVID‐19 outcomes were favorable, with no increased risk of severe COVID‐19. Prospective studies on immunotherapies are needed to help determine best treatment practices.